Effect of Speech Therapy on Bilabial Production in Children with Repaired Cleft Lip and Palate - Sushma Manjunath; Pushpavathi M; Manu Prasad S (Journal of All India Institute of Speech and Hearing, 2019)
The present study is aimed to provide periodic documentation on the effects of speech therapy on temporal parameters in children with repaired cleft lip and palate (RCLP). The study consisted of two groups; the clinical group consisted of four participants with RCLP, and the control group consisted of ten typically developing children (TDC), between the age of 4-7.11 years with Kannada as their native language. The stimuli consisted of meaningful, picturable, age-appropriate Kannada words with bilabials in the initial position which were uttered by the participants. The type of error, presence/absence of burst, burst duration (BD), voice onset time (VOT) and word duration (WD) were analysed at baseline, after the therapy sessions and after the intervention. Articulation therapy was provided in two phases:perception training and production training. The temporal parameters considered in the present study were measured after every phase of the intervention from the clinical group and were compared to the mean value obtained from the control group. Perceptual assessment was also done by the speech language pathologist (SLP) which indicated an improvement in the production of the target words. Inter-rater reliability of the samples indicated a substantial agreement (k=0.69). Baseline assessment of the clinical group indicated absence of burst in 12 of the target utterances. In instances where the burst was present, BD and VOT were observed to be shorter compared to the control group. WD was found to be varying, indicating the presence of articulatory errors. With every assessment, changes in the temporal parameters were noted and compared with that of the control group. The analysis after intervention phase 4 indicated the presence of burst, changes in BD, VOT and increase in WD when compared to the TDC indicating a positive outcome of speech therapy. The results of the present study provide evidence that working on improving articulation brings about changes in the temporal parameters of speech, indicating an overall benefit from articulatory therapy in children with RCLP.